For the Issue of Georgian Intervention and Annexation by Soviet Russia - Samsonia, Levan (COLLECTION OF SCIENTIFIC WORKS OF SOKHUMI UNIVERSITY, 2023)
One of the most difficult events in the history of Georgia is the violent Sovietization of the country by Bolshevik Russia in 1921. As a result, Georgia lost its sovereignty and a chance for the development as a European-type state. Study of the topic in historiography began immediately after the establishment of Soviet power in Georgia. Clearly, coverage of events was biased. From the beginning of the 90s of the XX century, from the restoration of state independence by Georgia, the situation has changed radically. A reassessment of the falsified history was on the agenda. This process continues today. Our goal is to evaluate this event objectively.